The Effect of Project Based-Learning Model Assisted by ESD-Based Student Worksheets on Critical Thinking Skills - Sopa Marwa, Neneng Widya; Agung Purwanto; Herlina Usman (Jurnal Elementaria Edukasia, 2025)
Critical thinking is an essential 21st-century skill to face the global economic era, but it is still low due to a lack of habituation in learning. This study aims to examine the influence of the Project Based Learning model assisted by LKPD based on Education for Sustainable Development on students' critical thinking skills in science learning in grade 5 of elementary school. The research method used was an experiment with a posttest-only control group design. The research sample consisted of 64 students both in the experimental class and in the control class, who were selected using the convenience sampling technique. The data analysis in this study uses descriptive and inferential statistics, with the t-test as a tool to test the hypothesis. The results showed that the average score of the experimental group was 83.81, while the control group obtained an average score of 72.42. The hypothesis test showed a Sig. (2-tailed) value of 0.000, which was smaller than 0.05 (α=0.05), so there was a significant difference in students' critical thinking skills between the experimental group and the control group. Thus, it can be concluded that the Project Based Learning model assisted by LKPD based on Education for Sustainable Development significantly affects students' critical thinking skills in science learning in grade 5 of elementary school. The results of this study are expected to encourage teachers to integrate the Project Based Learning model and LKPD based on Education for Sustainable Development in learning to improve students' critical thinking skills.